2023
DOI: 10.3389/fcimb.2023.1164654
|View full text |Cite
|
Sign up to set email alerts
|

Bacteria associated with glioma: a next wave in cancer treatment

Abstract: Malignant gliomas occur more often in adults and may affect any part of the central nervous system (CNS). Although their results could be better, surgical excision, postoperative radiation and chemotherapy, and electric field therapy are today’s mainstays of glioma care. However, bacteria can also exert anti-tumor effects via mechanisms such as immune regulation and bacterial toxins to promote apoptosis, inhibit angiogenesis, and rely on their natural characteristics to target the tumor microenvironment of hyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 68 publications
(72 reference statements)
0
1
0
Order By: Relevance
“…In glioma, a combination of Lactobacillus plantarum and Bifidobacterium bifidum has been shown to inhibit glioma growth by suppressing the phosphoinositide 3-kinase/serine-threonine kinase (PI3K/AKT) pathway [ 130 ]. This suggests that LAB-based microbial formulations or their metabolic byproducts, such as lactate, could be potential therapeutic options for glioma treatment [ 131 ]. However, some researchers indicated that lactate accumulated in gliomas could induce regional metabolic reprogramming and activate oxidative metabolism to protect GBM cells from nutrient deprivation-mediated cell death [ 132 , 133 ].…”
Section: Gut Bacteria and Cns Tumorsmentioning
confidence: 99%
“…In glioma, a combination of Lactobacillus plantarum and Bifidobacterium bifidum has been shown to inhibit glioma growth by suppressing the phosphoinositide 3-kinase/serine-threonine kinase (PI3K/AKT) pathway [ 130 ]. This suggests that LAB-based microbial formulations or their metabolic byproducts, such as lactate, could be potential therapeutic options for glioma treatment [ 131 ]. However, some researchers indicated that lactate accumulated in gliomas could induce regional metabolic reprogramming and activate oxidative metabolism to protect GBM cells from nutrient deprivation-mediated cell death [ 132 , 133 ].…”
Section: Gut Bacteria and Cns Tumorsmentioning
confidence: 99%